Chloramphenicol Mediates Superoxide Production in Photosystem II and Enhances Its Photodamage in Isolated Membrane Particles - Rehman, Ateeq Ur; Kodru, Sandeesha; Vass, Imre (Frontiers in Plant Science, 2016)
Chloramphenicol is an inhibitor of protein synthesis, which is frequently used to decouple photodamage and protein synthesis dependent repair of Photosystem II during the process of photoinhibition. It has been reported earlier that chloramphenicol is able to mediate superoxide production by transferring electrons from the acceptor side of Photosystem I to oxygen. Here we investigated the interaction of chloramphenicol with Photosystem II electron transport processes by oxygen uptake and variable chlorophyll fluorescence measurements. Our data show that chloramphenicol can accept electrons at the acceptor side of Photosystem II, most likely from Pheophytin, and deliver them to molecular oxygen leading to superoxide production. In addition, the presence of chloramphenicol enhances photodamage of Photosystem II electron transport in isolated membrane particles, which effect is reversible by superoxide dismutase. It is concluded that chloramphenicol acts as electron acceptor in Photosystem II and mediates its superoxide dependent photodamage. This effect has potential implications for the application of chloramphenicol in photoinhibitory studies in intact systems.